SAS 9.4 functions and CALL routines : reference (SAS documentation., 2014)
This book provides comprehensive information about the Base SAS functions and CALL routines. It will enable you to import and export macro variables, copy a record from one fileref to another, determine whether an argument is character or numeric, and more. --